No evidence for a functional role of bi-directional notch signaling during angiogenesis - Liebler, Sven Stefan; Feldner, Anja; Adam, M. Gordian; Korff, Thomas; Augustin, Hellmut; Fischer, Andreas (PLOS ONE, 2012)
The Delta-Notch pathway is a signal exchanger between adjacent cells to regulate numerous differentiation steps during embryonic development. Blood vessel formation by sprouting angiogenesis requires high expression of the Notch ligand DLL4 in the leading tip cell, while Notch receptors in the trailing stalk cells are activated by DLL4 to achieve strong Notch signaling activity. Upon ligand binding, Notch receptors are cleaved by ADAM proteases and gamma-secretase. This releases the intracellular Notch domain that acts as a transcription factor. There is evidence that also Notch ligands (DLL1, DLL4, JAG1, JAG2) are processed upon receptor binding to influence transcription in the ligand-expressing cell. Thus, the existence of bi-directional Delta-Notch signaling has been proposed. We report here that the Notch ligands DLL1 and JAG1 are processed in endothelial cells in a gamma-secretase-dependent manner and that the intracellular ligand domains accumulate in the cell nucleus. Overexpression of JAG1 intracellular domain (ICD) as well as DLL1-ICD, DLL4-ICD and NOTCH1-ICD inhibited endothelial proliferation. Whereas NOTCH1-ICD strongly repressed endothelial migration and sprouting angiogenesis, JAG1-ICD, DLL1-ICD and DLL4-ICD had no significant effects. Consistently, global gene expression patterns were only marginally affected by the processed Notch ligands. In addition to its effects as a transcription factor, NOTCH1-ICD promotes cell adhesion to the extracellular matrix in a transcription-independent manner. However, JAG1-ICD, DLL1-ICD and DLL4-ICD did not influence endothelial cell adhesion. In summary, reverse signaling of Notch ligands appears to be dispensable for angiogenesis in cellular systems.
Gesehen am 10.11.2018